1981
DOI: 10.2323/jgam.27.57
|View full text |Cite
|
Sign up to set email alerts
|

Chemotaxonomic and phenotypic characterization of the strains of species in the Flavobacterium-cytophaga complex.

Abstract: Quinone systems, DNA base composition, cellular fatty acid composition, and phenotypic characteristics of 41 strains of named Flavobacterium species, 10 strains of named Cytophaga species, and 16 isolates belonging to the Flavobacterium-Cytophaga complex were investigated. These strains were divided into two major groups on the basis of the quinone systems and DNA base composition: The ubiquinone system (Q-8 or Q-10) and high values in DNA base composition (64.1 to 69.2%) were found in one group. The strains i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(41 citation statements)
references
References 28 publications
1
40
0
Order By: Relevance
“…7 ) The quinone system was identified by the method of Oyaizu and Komagata. 8 ) Electron microscopic observation. The electron micrograph was taken on a model JEM-2000FXII transmission electron microscope (Nihon Densi Co.), after shadowing with 1 % tungsten phosphoric acid.…”
Section: Methodsmentioning
confidence: 99%
“…7 ) The quinone system was identified by the method of Oyaizu and Komagata. 8 ) Electron microscopic observation. The electron micrograph was taken on a model JEM-2000FXII transmission electron microscope (Nihon Densi Co.), after shadowing with 1 % tungsten phosphoric acid.…”
Section: Methodsmentioning
confidence: 99%
“…Some of these species were shown to grow not only aerobically but also anaerobically (Bachmann, 1955 ;Veldkamp, 1961). More recent taxonomic investigations have shown an overlap between the genera Cytophaga and Flavobacterium (Callies & Mannheim, 1978 ;Christensen, 1977 ;Hayes, 1977;Oyaizu & Komagata, 1981;Shewan & McMeekin, 1983). The bacteria in these groups were then called the Cytophaga-Flavobacterium complex, and included the genera Flexibacter, Microscilla, Sporocytophaga and Chitinophaga, which resemble 01032 0 1999 IUMS Cytophaga or Flavobacterium in their morphological and phenotypic characteristics (Christensen, 1977 ;Shewan & McMeekin, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Differential hydrolysis indicated that 2-OH 17 : 0, 3-OH iso-16 : 0 and 3-OH iso 17 : 0 were presumptively amide-linked, as well as ester-linked in smaller proportions. The presence of a complex pattern of fatty acids including straight-chain, branched (iso-and anteiso-) and hydroxylated fatty acids is a characteristic found in many species within the BacteroidesFlavobacterium-Cytophaga-Sphingobacterium group (Daneshvar et al, 1991;Fautz et al, 1979;Mayberry, 1980;Miyagawa & Suto, 1980;Miyagawa et al, 1979;Moore et al, 1994;Oyaizu & Komagata, 1981;Sakamoto et al, 2002;Shah & Collins, 1980Steyn et al, 1998;Urakami & Komagata, 1986). A detailed survey of the fatty acid patterns within this group is outside the scope of the present work, but it is obvious that features such as the presence or absence of significant amounts of unsaturated fatty acids or the relative abundance of iso-and anteiso-branched fatty acids of differing chain length can be used to differentiate different subgroups.…”
mentioning
confidence: 99%
“…The predominant quinone was MK-8, with smaller amounts of MK-7 and MK-9. Whereas those members of the Cytophaga-FlavobacteriumSphingobacterium subgroups produce either MK-6 or MK-7 as the major menaquinones (Nakagawa & Yamasato, 1993;Oyaizu & Komagata, 1981), it is not unusual to find not only longer chain (>MK-9), but also more than one isoprenologue in significant amounts in the Bacteroides-PrevotellaPorphyromonas-Tannerella subgroup (Shah & Collins, 1980;Sakamoto et al, 2002). It should be noted that some of the closest relatives of strain BN3 T , namely Tannerella forsythensis, Bacteroides merdae and Bacteroides distasonis (see below), produce menaquinones with 9-12 isoprenologues.…”
mentioning
confidence: 99%